Enhanced of analysed optimization learning model for multi product retail and distribution system - Anies Handayani; Sri Lestari; Budianto Taib; Abdul Rachman Saida (Jurnal Scientia, 2024)
This study aims to describe and analyze the supervision of Disnakertrans in fulfilling the minimum wage of Banggai Regency. This research is based on the curiosity of researchers on supervision related to the minimum wage received by the workforce amid economic growth and inflation as well as a fairly rapid industry in Banggai Regency. This research is a qualitative descriptive research with the sampling technique used is purposive sampling, The number of informants is 5 people. Data collection techniques are taken from interview and observation techniques which are then explained descriptively to obtain valid and accountable research results. The results of this study can be concluded that the supervision carried out by the Disnakertrans is still not good or ineffective, The form of supervision carried out by the Banggai Regency Disnakertrans is related to the fulfillment of wages including the preparation of work plans, the preparation stage, the implementation of activities, evaluation and reporting of supervisory results. Supervision is carried out on companies with a priority scale, namely companies that are considered often problematic, the results obtained from supervisory activities are recorded and reports are made, if there is a violation regarding MSEs, an inspection memorandum will be issued and can be reported to the authorities. There are several things that cause ineffective supervision, namely the lack of employees, while employers are increasing day by day in the Banggai Regency area, besides that direct supervision activities are rarely carried out in supervising the District Minimum Wage due to many agendas in the disnakrertrans, the large number of companies so that the period of time used is very much in conducting supervision and lack of facilities.